2006
DOI: 10.1080/09540120600643641
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and HIV infection in Russia

Abstract: Few studies have examined the personal and social consequences of stigma associated with HIV infection in Russia, a country with one of the most rapidly advancing HIV epidemics globally. By May 2005, Samara Oblast, Russia had 24,022 notified seropositive individuals. Focus-group discussions with randomly sampled seropositive and seronegative individuals, matched by age, gender and education were selected from the general population and used to provide an informal forum for discussion of attitudes to HIV and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Amirkhanian et al, 2011;Y. A. Amirkhanian, Kelly, & McAuliffe, 2003;Balabanova, Coker, Atun, & Drobniewski, 2006;Bobrova et al, 2006;King et al, 2013;Mimiaga et al, 2010;Rhodes et al, 2006;Rhodes et al, 2012;Sarang et al, 2010;Shilovskaya;Zigon, 2011). The similarities between this study's findings and those of the literature suggest that fear of being publicly identified as having HIV and of the discrimination that may result represents a significant barrier to accessing care and ART adherence for PLWHIV living in post-Soviet countries.…”
Section: Fear Of Disclosuresupporting
confidence: 45%
“…Amirkhanian et al, 2011;Y. A. Amirkhanian, Kelly, & McAuliffe, 2003;Balabanova, Coker, Atun, & Drobniewski, 2006;Bobrova et al, 2006;King et al, 2013;Mimiaga et al, 2010;Rhodes et al, 2006;Rhodes et al, 2012;Sarang et al, 2010;Shilovskaya;Zigon, 2011). The similarities between this study's findings and those of the literature suggest that fear of being publicly identified as having HIV and of the discrimination that may result represents a significant barrier to accessing care and ART adherence for PLWHIV living in post-Soviet countries.…”
Section: Fear Of Disclosuresupporting
confidence: 45%
“…From this initial study many lessons were learned and future research will focus on different sampling and attempts to determine a higher proportion of the risk factors among the sample. The venues in which the participants were recruited or participant comfort with reporting traditionally stigmatized behaviors could have been an issue [14,15]. While this study cannot determine etiology and causal relationships, the findings may assist HIV prevention efforts in demonstrating reluctance of persons to report their HIV related risk behaviors.…”
Section: Discussionmentioning
confidence: 87%
“…There are several barriers to HIV testing in Russia, which are associated with prevalent limited knowledge, misconceptions, and HIV stigma. 32 HIV testing is available at State AIDS Centers established in all regions and at some infectious diseases clinics. If an HIV infection is detected at these clinics, the person would be registered and referred to an AIDS Center for services.…”
Section: An Overview Of Presentationsmentioning
confidence: 99%